MTPHs, an Aesthetic Aspect of Local Architecture of Lenjanat - Mitra Shateri; Abbas Ali Ahmdi; Parisa Ranjbar (Iranian Journal of Archaeological Studies, 2014)
Among the variety and diversity of pigeon houses, Multi-Tier Pigeon Houses (MTPHs) are distinguished from the functional and aesthetic point of view and are considered as a specific local architectural sights of Lenjanat. However, few studies have been conducted to study this type of pigeon house and these constructs have remained unknown. In this study we have conducted library and field studies because of the profusion and diversity of these pigeon houses in the Mobarakeh region and Flavarjan region. The aim of this study is typology and classification of Multi-Tier Pigeon Houses based on plan, structural, and technical analysis of these constructs. The results of this study show that the congestion of these pigeon houses has been in Lenjanat, and the geographical and climatic conditions have been effective in construction of these structures. The necessity of typology and classification of these constructions is crucial in saving the native architectural heritage of these areas.